Patriarchal beliefs and perceptions towards women among Indian police officers: A study of Uttar Pradesh, India - Tripathi, Saumya (International journal of police science & management, 2020)
The objective of this study was to explore the association between patriarchal beliefs and perceptions regarding gender equity among Indian police officers. Using convenience and systematic random sampling, a cross-sectional survey was conducted with 190 police officers from Allahabad, Uttar Pradesh, India. The survey collected information about patriarchal beliefs, perception regarding gender equity, as well as social demographic characteristics including age, education, gender, work experience, working shifts/hours, place of residence and family system. Multiple linear regressions were used to predict patriarchal beliefs, utilizing the independent variable of perceptions regarding gender equity. Police officials held a high degree of patriarchal belief and inequitable perceptions regarding the gender roles of women. Multiple linear regression analysis, controlling for key sociodemographic variables, demonstrated a statistically significant association between the police officers’ patriarchal beliefs and their perceptions of gender equity. These findings emphasize the need for greater representation of female police officers and gender-inclusive training for all police officers in providing services to women. Gender-sensitive interventions may help facilitate positive change for police officers that hold strong patriarchal perceptions towards women and who may make it more difficult for women to successfully submit gender-based complaints.